2007
DOI: 10.2466/pr0.100.2.365-374
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nursing Counseling on Coping and Depression in Women Undergoing in Vitro Fertilization

Abstract: The purpose of present study was to evaluate the effectiveness of counseling provided by nurses on depression and coping strategies of infertile women undergoing in vitro fertilization (N=67). Of the 84 women who were interviewed, 30 were accepted as a comparison group, and 37 were included in the study group. The study group women were given counseling in addition to routine nursing care services, including group education and individual interviews about treatment and coping strategies. The nurses also provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…The mean difference between the 2 groups was not statistically significant in terms of the emotion-focused coping strategies. This finding is congruent with the findings of the studies conducted by Karlsen et al and Gurhan et al in which no statistically significant difference was found between intervention and control groups (24,26).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The mean difference between the 2 groups was not statistically significant in terms of the emotion-focused coping strategies. This finding is congruent with the findings of the studies conducted by Karlsen et al and Gurhan et al in which no statistically significant difference was found between intervention and control groups (24,26).…”
Section: Discussionsupporting
confidence: 83%
“…As Gurhun et al reported, infertility was a stressful event and IVF was perceived as a positive challenge with positive effects on infertile women (24). Before the intervention, the women in the two groups used positive reappraisal more than other coping strategies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations